1994
DOI: 10.1063/1.111807
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional model of ion dynamics during plasma source ion implantation

Abstract: Ion dynamics in the plasma sheath following the application of a negative voltage pulse to a two-dimensional target are modeled using a time-dependent, two-fluid simulation. The target considered is a square bar of infinite length. We find that the sheath focuses ions near to, but not on, the corner of the bar, resulting in an enhancement of the dose received there.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 8 publications
3
24
0
Order By: Relevance
“…We note that such a homogeneous plasma is often chosen as initial condition for PIII simulations. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] For a one-dimensional planar geometry, we discussed the differences between an established-sheath simulation and a homogeneous-plasma simulation in a previous article. 41 We concentrate our comparison on the time evolution of the ion current densities on the various parts of our structured surface.…”
Section: Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that such a homogeneous plasma is often chosen as initial condition for PIII simulations. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] For a one-dimensional planar geometry, we discussed the differences between an established-sheath simulation and a homogeneous-plasma simulation in a previous article. 41 We concentrate our comparison on the time evolution of the ion current densities on the various parts of our structured surface.…”
Section: Dynamicsmentioning
confidence: 99%
“…1 However, applications of this method are usually made to complex-formed objects, such that an understanding of the processes in two-or three-dimensional sheath expansion is required. The theoretical investigation of these processes has proceeded from a fluid description [3][4][5][6][7] of the plasma to the application of various hybrid particle-in-cell [8][9][10][11][12][13][14][15][16][17] algorithms. These studies reported on a number of phenomena: The strong electrical fields around convex corners focus the ion flux into the vicinity of but not immediately onto these corners; the ion flux peak broadens and moves away from the corner in time; the region of oblique impact angle increases with time; the flux around concave corners is diminished.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the dynamic properties of the plasma sheath is imperative for proper control over the implantation processing. Hence, many theoretical and experimental researches have been developed to study the plasma sheath structure [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Many works have investigated the collisional and magnetized plasma sheath containing ion and electron. Besides the works studying two-component plasma sheath composed of ion and electron, the investigation of multi-component plasma sheath has recently drawn considerable attention [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. For example, experimental investigation of plasma sheath containing two positive ions can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional model can be used for the case of planar, cylindrical or spherical target [1,12,16,17,25] . For targets of complex shape, such as a square bar [18,19,24] , a convex or concave wedge [8] , and trench-shaped targets [20,23] , two-dimensional model should be adopted.In this paper, based on the PSII researches in our laboratory, we will simply review the theoretical studies on the ion sheath dynamics during the PSII process, which have made great progress in recent years. Concentration is focused on the various models for the calculation of ion sheath dynamics in PSII, including comparisons of these models and their applicability for different cases.…”
mentioning
confidence: 99%